Autoinduced Catalysis and Inverse Equilibrium Isotope Effect in the Frustrated Lewis Pair Catalyzed Hydrogenation of Imines. Issue 22 (15th April 2015) - Tussing, Sebastian; Greb, Lutz; Tamke, Sergej; Schirmer, Birgitta; Muhle‐Goll, Claudia; Luy, Burkhard; Paradies, Jan
Abstract The frustrated Lewis pair (FLP)‐catalyzed hydrogenation and deuteration of N‐benzylidene‐tert‐butylamine (2) was kinetically investigated by using the three boranes B(C6F5)3 (1), B(2, 4, 6‐F3‐C6H2)3 (4), and B(2, 6‐F2‐C6H3)3 (5) and the free activation energies for the H2 activation by FLP were determined. Reactions catalyzed by the weaker Lewis acids 4 and 5 displayed autoinductive catalysis arising from a higher free activation energy (2 kcal mol−1) for the H2 activation by the imine compared to the amine. Surprisingly, the imine reduction using D2 proceeded with higher rates. This phenomenon is unprecedented for FLP and resulted from a primary inverse equilibrium isotope effect.